The Effects of Neuromuscular Electrical Stimulation (NMES) on Muscle Mass, Muscle Strength, and Functional Ability in The Elderly: A Literature Review - Kadek Dwi Wira Sanjaya; I Ketut Gede Agus Budi Wirawan (CV. Inara, 2026)
Sarcopenia is characterized by a loss of muscle in the elderly population with correlative muscle function loss and decreased mobility and independence, and it is associated with increased metabolic and cardiovascular risk. Physical activity is the foundation for prevention and treatment, yet numerous older people are unable to exercise sufficiently due to acute or chronic illnesses, neurological diseases, pain, anxiety, fear of falling, or demotivation. Neuromuscular electrical stimulation (NMES) might be the alternative or add-on treatment as it elicits muscle contractions with very little voluntary demand. This review examined the impact of NMES on muscle mass/size, muscle strength, functional capacity, and plausible mechanisms in elderly subjects. This study used a literature review from PubMed and ScienceDirect, identifying 108 records and including 38 eligible studies on NMES in older adults, with findings synthesized descriptively due to heterogeneity in protocols and outcomes. Overall, NMES was frequently reported to increase or at least maintain muscle mass or size, often in the quadriceps, and to reduce disuse atrophy during immobilization or critical illness, including ICU and acute heart failure settings, particularly when combined with early rehabilitation. Several studies also reported improvements in maximal isometric strength and functional outcomes such as mobility, balance, and gait. Proposed mechanisms include activation of anabolic signaling (IGF-1/PI3K/mTOR), enhanced regeneration markers, and reduced catabolic gene expression (FOXO1A, MSTN, MAFbx, MuRF1), without clear increases in oxidative stress in some studies. NMES appears promising, but standardized dosing and outcomes are needed